City Charter and Revised Ordinances of the City of Fall River, with Special Statutes Relating to the City, and an Appendix Page 158, Image 162 (1887) Ordinance so the City of Fall River, Streets Use. Revised Ordinance. Discharge of Firearms. § 20. - (:unkn) unknown (General Publisher, 1887)
No person shall, except in the performance of some legal duty, discharge any gun, pistol or firearm in any street or public place, or within fifty rods of any dwelling house.
--
Keywords: DISCHARGE